Peningkatan Kemampuan Mahasiswa dalam Membaca Gambar Proyeksi Menggunakan Pembelajaran Discovery Learning Dengan Media Model - Muhammad Khumaedi (Universitas Negeri Malang, 2016)
This experimental study aims at finding out whether discovery learning using model media improves students' ability in reading projection drawing. Utilizing pretest-posttest design, the study involved 30 students in each of the treatment and the control groups. Result of descriptive and t-test analyses reveal that discovery learning improves the students' ability in reading projection drawing and that it is a better learning model than reception learning.